2020
DOI: 10.1080/14992027.2020.1813338
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of data from the International Outcome Inventory for Hearing Aids (IOI-HA) using Bayesian Item Response Theory

Abstract: Objective: IOI-HA response data are conventionally analysed assuming that the ordinal responses have interval-scale properties. This study critically considers this assumption and compares the conventional approach with a method using Item Response Theory (IRT). Design: A Bayesian IRT analysis model was implemented and applied to several IOI-HA data sets. Study sample: Anonymised IOI-HA responses from 13273 adult users of one or two hearing aids in 11 data sets using the Australian English, Dutch, German and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…As it has recently been pointed out (Leijon et al 2020) that IOI-HA does not behave well when handled as a metric scale, we, therefore, applied the item specific category weights suggested in Leijon et al (2020) as a supplementary analysis and repeated the main analysis on the resulting IOI-HA scores. Moreover, as an additional sensitivity analysis, we applied ordinal logistic regression to the raw IOI-HA scores to investigate if this resulted in consistent estimates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As it has recently been pointed out (Leijon et al 2020) that IOI-HA does not behave well when handled as a metric scale, we, therefore, applied the item specific category weights suggested in Leijon et al (2020) as a supplementary analysis and repeated the main analysis on the resulting IOI-HA scores. Moreover, as an additional sensitivity analysis, we applied ordinal logistic regression to the raw IOI-HA scores to investigate if this resulted in consistent estimates.…”
Section: Discussionmentioning
confidence: 99%
“…The results from the regression analyses are presented in Table 4. For comparison, results from the corresponding regression models on the IOI-HA with the weights suggested by Leijon et al (2020) are reported in Supplementary Table 1. This sensitivity analysis and the analysis applying ordinal logistic regression instead (results not shown), resulted in estimates consistent with the main analysis.…”
Section: Factors Associated With Total Ioi-ha Factor 1 and Factor 2 Scoresmentioning
confidence: 99%
“…Researchers have generally used the mean scores to interpret the results of IOI-HA. However, as the IOI-HA results in ordinal data, the use of median scores of each item and total scores for the overall scores may be more appropriate [ 42 ]. To ensure backward compatibility of the data with previous literature, we also report the mean IOI-HA scores.…”
Section: Methodsmentioning
confidence: 99%
“…IOI-HA was developed over 20 years ago without the use of ITI, and all previous studies (Br€ annstr€ om and Wennerstr€ om 2010; Chu et al 2012;Cox and Alexander 2002;Jespersen, Bille, and Legarth 2014;Kramer et al 2002;Pavia et al 2017) that examined the psychometric properties of IOI-HA except the recent international study (Leijon et al 2020) have applied parametric methods such as PCA. Considering this, to allow maximum inter-study compatibility, the statistical analysis in this study falls generally in line with the procedure applied by Cox and Alexander (2002) in the original IOI-HA study.…”
Section: Discussionmentioning
confidence: 99%